Ion transfer across liquid|liquid interface under forced hydrodynamic conditions. I: Digital simulations - Ovejero, Juan Manuel (2012)
In this paper, we present the general equations for a model that describes ion transfer reactions across the oil|water interface assisted by a ligand, under forced hydrodynamic conditions. Our analysis is mainly focused on the effect of mechanical stirring of the aqueous or organic phase during the potential sweep, and its influence on the limiting diffusion currents. The model was solved numerically using explicit finite difference; the results of digital simulations are obtained for simple and facilitated ion transfer. The corresponding transfer mechanism was analyzed in terms of the current-potential profiles, concentration profiles and interfacial distributions, obtained from digital simulations.